Antibacterial Activity of Endophytic Fungus Isolates of Mangrove Fruit (Sonneratia alba) Against Staphylococcus aureus and Esherichia coli - Sesilia Rante Pakadang; Ismat Marsus; Ihsanawati Ihsanawati (JURNAL INFO KESEHATAN, 2021)
Endophytic fungi live and associate in plant tissues and have a mutualistic relationship. Endophytic fungi produce various compounds such as steroids, terpenoids, phenolics, alkaloids which are the same as secondary metabolites from their host plants. The objective of this study is to isolate and identify endophytic fungi from mangrove fruit (Sonneratia alba) and to determine the antibacterial activity of endophytic fungi isolates against the growth of Staphylococcus aureus and Escherichia coli. The type of research is pre-experimental design, one shoot case study. The methods used are isolation, identification and agar diffusion. The pieces of mangrove fruit were disinfected and then cultured on SDA media to grow endophytic fungi isolates. The isolates were cultured repeatedly until pure isolates were obtained. The test of isolate activity against antibacterial was determined by the agar diffusion method with the test material of 2 isolates of endophytic fungi on Nutrient Agar (NA) media. The results showed that the mangrove fruit (Sonneratia alba) produced two isolates of endophytic fungi that could inhibit the growth of Staphylococcus aureus and Escherichia coli. It was concluded that the mangrove fruit culture produced 2 isolates, which are isolate 1 Aspergillus niger and isolate 2 Aspergillus flavus. Isolate 1 and isolate 2 had the potential as antibacterial against the growth of Staphylococcus aureus and Escherichia coli. Isolate 2 was more effective than isolate 1 in inhibiting the growth of Staphylococcus aureus. It is recommended to test the pharmacological and microbiological activity of the findings of isolates 1 and 2 in vivo.